1994
DOI: 10.1002/mds.870090216
|View full text |Cite
|
Sign up to set email alerts
|

Development of resistance to botulinum toxin type A in patients with torticollis

Abstract: Between 1984 and 1992, 559 patients with torticollis were treated with botulinum toxin type A (btx) injections. Twenty-four of these 559 patients (4.3%) had serological evidence of antibodies to btx by mouse neutralization assay. Some of the 559 patients had only one or two injection series, whereas others were lost to follow-up, so that the actual prevalence of serologically detectable antibodies may be higher than 4%. In addition, some patients who improved after btx injections lost benefit and stopped devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
175
2
11

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 365 publications
(193 citation statements)
references
References 16 publications
5
175
2
11
Order By: Relevance
“…39,45,59 The clinical reestablishment of muscle function after BoNT-A injections requires repeated injections over long periods. 49,50 The onset of resistance to botulinum toxin over time may be due to the immunological properties of the toxin that lead to the stimulation of antibody production, thus rendering further treatments ineffective. [48][49][50][51] Greene and Fahn 49 found that patients resistant to botulinum toxin received more booster injections early after treatment, as well as higher doses compared with responsive patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…39,45,59 The clinical reestablishment of muscle function after BoNT-A injections requires repeated injections over long periods. 49,50 The onset of resistance to botulinum toxin over time may be due to the immunological properties of the toxin that lead to the stimulation of antibody production, thus rendering further treatments ineffective. [48][49][50][51] Greene and Fahn 49 found that patients resistant to botulinum toxin received more booster injections early after treatment, as well as higher doses compared with responsive patients.…”
Section: Discussionmentioning
confidence: 99%
“…49,50 The onset of resistance to botulinum toxin over time may be due to the immunological properties of the toxin that lead to the stimulation of antibody production, thus rendering further treatments ineffective. [48][49][50][51] Greene and Fahn 49 found that patients resistant to botulinum toxin received more booster injections early after treatment, as well as higher doses compared with responsive patients. These authors, therefore, recommended that the lowest possible effective dose should be used, with treatment intervals of at least 3 months, and that booster injections be avoided.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unclear where the common practice of administering BoNT not more frequently than every 3 months was based, because the early studies of immunoresistance were in the cervical dystonia, not stroke, population. 43 Although no prospective investigation of antibody formation to repeated BoNT injection has been reported, it is estimated that the incidence of antibody to BoNT in the spastic hypertonia population is <1%, which is lower than in cervical dystonia. 44 Repeated BONT injections appear to result in sustained reduction of spastic hypertonia.…”
Section: Clinical Issues In the Use Of Bontmentioning
confidence: 99%
“…Using an older formulation, it was estimated to occur in at least 5%-10% of patients with cervical dystonia (11). Factors that increase the risk for antibody formation include higher doses and short intervals between doses (12)(13)(14). With the new formulation and the relatively low doses used in migraine treatment (see below), this complication is unlikely to occur.…”
Section: Btx Type a (Btx-mentioning
confidence: 99%